Correction: Water-induced formation of an alkali-ion dimer in cryptomelane nanorods. Issue 27 (2nd July 2020) - Cheng, Shaobo; Sharma, Vidushi; Poyraz, Altug S.; Wu, Lijun; Li, Xing; Marschilok, Amy C.; Takeuchi, Esther S.; Takeuchi, Kenneth J.; Fernández-Serra, Marivi; Zhu, Yimei
Abstract : Correction for 'Water-induced formation of an alkali-ion dimer in cryptomelane nanorods' by Shaobo Cheng et al., Chem. Sci., 2020, 11, 4991–4998, DOI: ; 10.1039/D0SC01517B .